Carbon Nanotube-Based Drug Delivery System Increases Drug Content and Promotes Immune Response in Mandarin Fish - Yijun Jia; Zhao Zhao; Leyang Chen; Yongqi Liu; Bin Zhu (Fishes)
A number of viral diseases have significantly impeded the growth of the aquaculture industry. Antiviral drugs represent an effective means of controlling infection. However, the efficacy of the entire therapeutic process is contingent upon the availability of an efficient delivery system. This study selected three common antiviral drugs and constructed corresponding drug delivery systems utilising single-walled carbon nanotubes (SWCNTs) as carriers. The reliability of carbon nanotubes as delivery carriers was evaluated by detecting the therapeutic effect on infectious splenic and renal necrosis virus (ISKNV). The findings demonstrated that SWCNTs can effectively enhance the absorption of the three drugs into the body, prolong their metabolic half-life, and improve the survival rate of fish infected with ISKNV. The Ribavirin-SWCNTs (RBV-SWCNTs) group exhibited the most pronounced protective effect, with a mortality rate of less than 25%. It was observed that SWCNTs facilitated the rapid transportation of ribavirin, with the drug content in the RBV-SWCNTs group being approximately double that of the free ribavirin group. Furthermore, this system markedly diminished the viral load, augmented enzyme activities, and elevated antiviral gene expression. This study indicated that carbon nanotubes are optimal carriers for antiviral drugs, which have considerable potential as a delivery vehicle for antiviral drugs to prevent viral infections in aquaculture.